If x-y+z=10 and -x+y=3 what is the value of z?

A) 13

B) 7

c) 10/3

D) -7

E) -13

–*x* + *y* = 3 can be rewritten: –(*x* – *y*) = 3. That means that *x* – *y* = –3.

So *x* – *y* + *z* = 10 can be rewritten: –3 + *z* = 10. That means *z* = 13.

Skip to content

If x-y+z=10 and -x+y=3 what is the value of z?

A) 13

B) 7

c) 10/3

D) -7

E) -13

–*x* + *y* = 3 can be rewritten: –(*x* – *y*) = 3. That means that *x* – *y* = –3.

So *x* – *y* + *z* = 10 can be rewritten: –3 + *z* = 10. That means *z* = 13.